Effect of Ga2O3 Addition on the Properties of Garnet-Type Ta-Doped Li7La3Zr2O12 Solid Electrolyte - Yusuke Yamazaki; Shotaro Miyake; Keigo Akimoto; Ryoji Inada (Batteries, 2022)
Garnet-type Ta-doped Li7La3Zr2O12 (LLZO) ceramic solid electrolytes with Ga2O3 additive were synthesized using a conventional solid-state reaction process. When the amounts of Ga2O3 additive were below 2 mol %, the sintered sample has a dense structure composed of grains with an average size of 5 to 10 μm, whereas 3 mol % or more Ga2O3 addition causes a significant increase in grain size above several 10 to 100 μm, due to high-temperature sintering with a large amount of liquid Li-Ga-O phase. At room temperature, the highest total (bulk + grain-boundary) ionic conductivity of 1.1 mS cm−1 was obtained in the sample with 5 mol % Ga2O3 addition. However, this sample was shorted by Li dendrite growth into solid electrolyte at a current density below 0.2 mA cm−2 in galvanostatic testing of the symmetric cell with Li metal electrodes. The tolerance for Li dendrite growth is maximized in the sample sintered with 2 mol % Ga2O3 addition, which was shorted at 0.8 mA cm−2 in the symmetric cell. Since the interfacial resistance between Li metal and solid electrolyte was nearly identical among all samples, the difference in tolerance for Li dendrite growth is primarily attributed to the difference in microstructure of sintered samples depending on the amounts of Ga2O3.